Pengaruh Edukasi Berbasis Video Terhadap Pengetahuan Penggunaan Insulin, Pola Makan, Manajemen Diri dan Glukosa Darah Puasa Pada Pasien Diabetes - Bella Fevi Aristia; Tiara Putri Hartanto; Brelianty Nevy Tyara CP; Eka Putri Nurhidayah; Adinugraha Amarullah; Alfu Laila (INPHARNMED Journal (Indonesian Pharmacy and Natural Medicine Journal), 2026)
Background: Although various educational strategies have been implemented for patients with diabetes mellitus (DM), many challenges still exist, including inadequate glycemic control. This is due to patients' lack of understanding about DM management. Objective: This study examined the effect of video education on knowledge of insulin use, diet, diabetes self-management, and fasting blood glucose in insulin-treated patients with Type 2 DM. Methods: This quasi-experimental study employed a pretest-posttest design with a control group. Prospective data were collected from June to August 2025 using purposive sampling. A total of 60 patients with insulin-treated Type 2 DM who met the inclusion criteria participated. The sample was divided into control and treatment groups of 30 patients each. Participants in the intervention group received video- based education on insulin use, diet, and diabetes self-management. Data were collected using validated questionnaires assessing insulin knowledge, dietary patterns, and the Diabetes Self-Management Questionnaire (DSMQ). Results: The intervention group showed significant improvements in all outcomes. Median insulin knowledge scores increased from 13 (10–17) to 17 (14–18) (p=0.001), dietary pattern scores increased from 63 (56–74) to 70 (61–78) (p<0.001), and self-management scores increased from 38.72 to 41.57 (p<0.001). Median fasting blood glucose levels decreased from 161 mg/dL (82–305) to 145 mg/dL (89– 239) (p=0.010). Conclusion: Video-based education effectively improves knowledge, dietary patterns, self- management, and glycemic control in insulin-treated patients with type 2 DM.